CO GENETIC CR-TOURMALINE AND EMERALD IN THE NOVO CRUZEIRO PEGMATITE FIELD (MINAS GERAIS, BRAZIL) - Horn, Heinrich Adolf; Fuchs, Yves; Fourdrin, Chloe; Grenèche, Jean Marc; Boudouma, Omar (Geochimica Brasiliensis, 2022)
The Novo Cruzeiro pegmatite field in Minas Gerais (Brazil) between Téofilo Otoni and the Jequitinhonha River belongs to the areas of the EBPP with tourmaline and emerald occurrences. The pegmatites show beside of coloured tourmalines, Cr rich black tourmaline cogenetic with Cr-emerald. General crystallization conditions of the pegmatites are given with due to the obtained data, important changes during final phase of tourmaline crystallisation causing variations in tourmaline chemistry and reflect differences in the chemistry of the participating fluids. The deposition of tourmaline ceased and after a period of cocristallization, emerald was the only mineral that formed then. The obtained information suggests a crystallization sequence from tourmaline over tourmaline-emerald to emerald. A part of B and Fe may come from the host rock, Be and B also from the intrusive granites and Cr from regional mafic to ultramafic rocks like amphibolite or Bt-Qu-schist.